2016
DOI: 10.1007/s12264-016-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Rab27b is Involved in Lysosomal Exocytosis and Proteolipid Protein Trafficking in Oligodendrocytes

Abstract: Myelination by oligodendrocytes in the central nervous system requires coordinated exocytosis and endocytosis of the major myelin protein, proteolipid protein (PLP). Here, we demonstrated that a small GTPase, Rab27b, is involved in PLP trafficking in oligodendrocytes. We showed that PLP co-localized with Rab27b in late endosomes/lysosomes in oligodendrocytes. Short hairpin-mediated knockdown of Rab27b not only reduced lysosomal exocytosis but also greatly diminished the surface expression of PLP in oligodendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Some cells use their lysosomes as a regulatory compartment for secretion (Blott & Griffiths, 2002;Holt, Gallo, & Griffiths, 2006;van der Sluijs, Zibouche, & van Kerkhof, 2013;Zhang et al, 2007). Recently, the roles of lysosomal exocytosis in myelin formation were investigated (Chen et al, 2012;Feldmann et al, 2011;Shen et al, 2016;Su et al, 2016). In this study, our data suggested that P2X4R is mainly localized in lysosomes of Schwann cells and P2X4R can be transported to the plasma membrane via lysosomal exocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cells use their lysosomes as a regulatory compartment for secretion (Blott & Griffiths, 2002;Holt, Gallo, & Griffiths, 2006;van der Sluijs, Zibouche, & van Kerkhof, 2013;Zhang et al, 2007). Recently, the roles of lysosomal exocytosis in myelin formation were investigated (Chen et al, 2012;Feldmann et al, 2011;Shen et al, 2016;Su et al, 2016). In this study, our data suggested that P2X4R is mainly localized in lysosomes of Schwann cells and P2X4R can be transported to the plasma membrane via lysosomal exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry was performed as previously described (Shen et al, ). Briefly cultured Schwann cells were fixed with 4% paraformaldehyde for 20 min, then blocked with Immunol Staining Blocking Buffer (Beyotime, Haimen, Jiangsu Province, China) for 1 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Following the treatment, 2 Â 10 7 cells per treatment were resuspended in 250 mmol/L sucrose/10 mmol/L Tris/HCl buffer solution, which were then disrupted by sonication with two 15-second pulses (Sonics and Materials VCX 600 Watt; ref. 21). The disrupted cells were then subjected to rotation (1,200 Â g for 15 minutes) to remove nuclei and cell debris, and the supernatants were submitted to centrifugation at 30,000 Â g for 30 minutes to achieve the enriched lysosome fraction.…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…An increase in transportation of myelin proteins to the plasma membranes may be essential for E2-induced remyelination, which is dependent on the E2-induced increase in the number of lysosomes. Lysosome of oligodendrocytes and Schwann cells contain abundant myelin proteins, such as PLP and P0, playing an important role in the remyelination of injured nerve via lysosomal exocytosis ( Chen et al, 2012 ; Shen et al, 2016 ; Su et al, 2016 ). We also found that the expression of these two lysosome markers LAMP-1 and myelin protein P0 were significantly increased in E2-treated rats compared with those in vehicle-treated rats after sciatic nerve crush injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, accumulating studies have shown that lysosomes in specific cells function in secretory process, which can package bioactive substances and release contents via exocytosis ( Blott and Griffiths, 2002 ; Zhang et al, 2007 ; Ballabio and Gieselmann, 2009 ). A growing number of studies, including our recently study ( Chen et al, 2012 ; Shen et al, 2016 ; Su et al, 2016 ) have shown that the lysosomes of OLs and SCs contain abundant myelin proteins and play an important role in remyelination of injured nerves via the lysosomal exocytosis. In this paper, we would also investigate whether estrogen regulates myelination by enhancing lysosomal exocytosis of Schwann cells.…”
Section: Introductionmentioning
confidence: 96%